Metacognitive Inquiry-Based Science Modules: A Need Analysis of Elementary Pre-Service Teachers’ Science Process Skills - Syahriani Yulianci; Nurjumiati Nurjumiati; Baiq Dina Hardianti (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Science Process Skills (SPS) are essential competencies for prospective elementary school teachers, yet PGSD students often have limited opportunities to develop these skills through inquiry-based learning. This study analyzed students’ needs for developing an inquiry-based science module with a metacognitive orientation to enhance SPS. A quantitative descriptive survey was conducted with 60 PGSD students who had completed a science course. Data were collected using a needs analysis questionnaire covering five student characteristics and three SPS need dimensions. Descriptive statistics, Pearson correlation, item-level correlation, and the Mann–Whitney U test were employed. Learning styles and preferences showed the highest mean score (M = 3.031), whereas learning experience had the lowest (M = 2.292), indicating limited exposure to laboratory and inquiry-based learning. All SPS need dimensions were rated very high, with module requirements obtaining the highest mean score (M = 3.654). Although no significant relationships were found between overall student characteristics and SPS needs, item-level analysis revealed a positive correlation between the ability to relate science concepts to everyday life and awareness of SPS gaps (r = 0.319, p = 0.027), and a negative correlation between difficulties in understanding abstract concepts and module requirements (r = −0.397, p = 0.005). Students with lower academic ability reported significantly greater module needs (p = 0.012). These findings support the development of a differentiated inquiry-based science module integrated with metacognitive strategies to improve SPS among prospective elementary school teachers.